TEPUNG BUAH NAGA MERAH DAN OLAHRAGA MEMPERBAIKI GLUKOSA DARAH DAN PROFIL LIPID DARAH PADA TIKUS OBES - Febriani, Wiwi; Sulaeman, Ahmad; Setiawan, Budi (Jurnal Gizi dan Pangan, 2016)
The objective of this study was to analyze the effects of feeding flour-based red dragon fruit and exercise to blood glucose and lipid profile in obese rats. Total of 20 males Sprague-Dawley were divided into five groups: standard diet (SD), high fat diet (HFD), high fat diet + exercise (HFD+E), high fat diet + red dragon fruit flour (HFDRD), and high fat diet + red dragon fruit flour + exercise (HFDRD+E). The intervention was carried out for four weeks after 18 weeks fattening periode. The results showed that red dragon fruit and exercise significantly decreased blood glucose, total cholesterol (TC), trygliseride (TGA), and LDL-chlesterol (LDL-C) (p<0.05), but not for HDL-cholesterol. The HFDRD+E group significantly (p<0.05) had highest decreased of blood glucose, TC. In conclusion, red dragon fruit and exercise have a potential effect to improve hyperglicemic condition and dyslipidemic condition.Keywords: blood glucose, lipid profile, obese rats, red dragon fruit